Cu atomic chains supported on β-borophene sheets for effective CO2 electroreduction. Issue 23 (6th June 2018) - Shen, Haoming; Li, Yawei; Sun, Qiang
Abstract : Cu atomic chains supported on β-borophene sheets can break the scaling relationship and enhance CO2 electroreduction. Abstract : The good performance of Cu displayed in CO2 conversion promotes the study on how to disperse Cu into 2D materials for better catalysis. Inspired by the recent studies on new 2D porous B sheets [ Angew. Chem., Int. Ed., 2017, 56, 10093; Adv. Mater ., 2018, 30, 1704025; Phys. Rev. Lett., 2017, 118, 096401], here for the first time we have explored the catalytic properties of Cu atomic chains on β-borophene sheets, and have found that the Cu–B sheet can break the scaling relationship through providing secondary adsorption sites, thus leading to small overpotentials in the preferable reaction pathway CO2 → COOH* → CO* → CHO* → CH2 O* → CH3 O* → CH3 OH. The Cu atomic chains also lower the energy barrier by forming assistant adsorptions of H*. Electronic structure analyses further show that the Cu atomic chain structure stabilizes the CHO* bonding through an enhanced σ bonding–π back-bonding mode. Our study not only sheds light on the design of new catalysts for effective CO2 conversion but also expands the applications of B sheets.